Kajian Distribusi dan Daya Layan Minimarket di Kecamatan Jekulo Kabupaten Kudus - Haida, Falistya Ainissalama, Drs. Priyono, M.Si, Dra. Umrotun, M.Si (2015)
Community needs for information about the minimarket in District Jekulo Kudus Regency indispensable. Through this thesis the author will provide information such as map and Power Distribution Study of Self Minimarket in District Jekulo Kudus, including information contained typology minimarket. This mapping all the information will be more easily understood. The problem in this research is the spread of the location minimarket in District Jekulo Kudus Regency uneven. This study aims to map the location of minimarket and a minimarket include maid power to the community and display information system typology minimarket. This research area is the District Jekulo Holy District. Variables used consists of a GPS plotingan the data directly in the field, spatial data and attribute data. Spatial data is data that beracuan on location. Attribute data is data obtained from secondary data to support in providing direction laying of new minimarkets. Processing of the data in this study begins by plotting GPS data into ArcGIS 9.3 and then perform Power Distribution and Self Assessment Minimarket with buffering, after the display forms of information systems at the map and determine recommendations minimarket development time when that will come by considering population density, mean average people or households, road conditions, and the villages of the district transportation route Jekulo Holy District. From writing thesis can be concluded that the distribution of minimarket in District Jekulo not evenly distributed, there should be additional minimarket in villages unserved and the importance of the type of information system services and merchandise to monitor the development of the minimarket. Keywords: Mapping, Distribution, Power Layan, Minimarket.